EFFORTS TO IMPROVE THE ROLE OF TRAFFIC UNITS IN BEKASI CITY POLRES IN THE IMPLEMENTATION OF PATUH JAYA OPERATIONS IN THE PANDEMIC TIME OF COVID-19 - M.NOORBUWONO ERCHAKA PUTRO (Advances in Police Science Research Journal, 2019)
This research is motivated by the holding of Operation Patuh Jaya in 2020 in the Bekasi City Metro Police Region which will be held from July 23 to August 5, 2021. However, there is a new situation, namely the emergence of thepandemic Covid-19, in which there is the latest regulation in the form of implementing protocols. so that the implementation of the Patuh Jaya Operation in 2020 is different from the operation in previous years. Therefore, a study was conducted that aims to determine the role of Traffic Unit in the implementation of Operation Patuh Jaya in 2020, the factors that affect the Traffic Police Satlantas Metro Bekasi City in the implementation of Operation Patuh Jaya in 2020, and any efforts to optimize the role of Satlantas. in the implementation of Operation Patuh Jaya in the future. The results of the study found that the implementation of the Patuh Jaya Operation this year was not optimal due to the covid-19 pandemic. Factors influencing the implementation of Operation Patuh Jaya in 2020 which was carried out by the Metro Bekasi City Police Traffic Unit, were influenced by eight (8) factors both internally and externally with three (3) supporting factors and five (5) inhibiting factors. . Based on the results of the study, the authors suggest to prepare all the needs for all supporting tools in the implementation of the Patuh Jaya Operation, conduct training or training on training for members who have just carried out the tasks of the Patuh Jaya Operation, Distribute the allocation funds provided by Polda Metro Jaya to all members involved , this can be done by re-listing all the members involved and re-distributing the funds that fell evenly to all members involved, continuing to carry out direct counseling activities on a regular basis by continuing to apply health protocols or it can be carried out in away virtual, forming a separate task force in specifically to remind road users regarding compliance in implementing the Covid-19 Prokes, and continue to take action in the form of fines for violators on a priority scale while still implementing health protocols.